Development of a combined CMV-UL97 C592F and CMV-UL54 T503I resistance mutation during ganciclovir treatment in a kidney transplant recipient. Issue 4 (October 2019) - Karrasch, Matthias; Michel, Detlef; Schneider, Sibylle; Baier, Michael; Busch, Martin
Abstract : N/A: In CMV high-risk kidney transplant recipients (KTR), recommended antiviral human cytomegalovirus (CMV) treatment can lead to nephrotoxicity and antiviral resistance. In this case report, we report the development of a combined CMV-UL97 C592F and CMV UL54 T503I resistance mutation in a high-risk KTR most probably linked to the previous treatment with valganciclovir (valGCV) and ganciclovir (GCV). Routine CMV screening, in addition with testing of CMV immunity and applied stewardship programs for ganciclovir might have been helpful in preventing the development of these mutations in this patient.